The body cannot be cheated: sexual practices and modern contraceptive use among street-involved young people in two South West States in Nigeria [version 2; peer review: 1 approved, 2 approved with reservations] - Atinuke O. Olaleye; Mary O. Obiyan; Morenike O. Folayan; Macellina Y. Ijadunola (Open Research Africa)
Background Young people aged 10–24 years constitute about one-third of the total population of Nigeria. Street-involved young people (SIYP) face a double burden of living condition instability and lack of adequate parental monitoring. This leaves them vulnerable to poor sexual and reproductive health (SRH) choices and behaviour. Risky sexual behaviour with poor access to SRH information and interventions increases their vulnerability to adverse SRH outcomes. This study explored the use of modern contraceptives and sexual practices among male and female SIYP (10–24 years) in Nigeria. Methods This qualitative study used an exploratory research design to guide the development of the focus group discussion (FGD) and in-depth interview (IDI) guides. Participants were asked questions on background information, lived experiences and SRH practices. The FGDs were stratified by sex and age. Both FGD discussions and IDI interviews were recoded; transcripts were transcribed and translated from local dialect into English language. Content analysis was conducted thematically with the aid of NVivo. Results A total of 17 IDIs and 11 FGDs were conducted109 participants. Awareness and use of modern contraceptives varied among sexually active SIYP. Commonly methods included condoms, oral pills, and emergency contraceptives, while knowledge of IUDs, female condoms, and injectables was limited. Inconsistent use stemmed from poor access, financial barriers, and myths. Condoms were underused due to stigma linking them to disease or immorality. Early sexual debut (ages 10–15) was influenced by peer pressure or sexual violence. Sexual activity was often viewed as normal—for fun, affection, or survival—with transactional sex common among young women. Reports of same-sex relationships were rare. Conclusions The study concludes that SIYP are generally aware of modern contraceptives, particularly male condoms, but usage is inconsistent and inadequate. These behaviours were driven by survival struggles, increasing vulnerability to negative SRH outcomes. To address these gaps, actions are recommended to dispel myths, increase contraceptive knowledge and uptake, and promote safe sex practices, improving both health and socio-economic well-being for SIYP.